Multi-criteria decision making in formation of balanced portfolio of npp safety improvement projects = Многокритериальное принятие решений при формировании сбалансированного портфеля проектов повышения безопасности АЭС - Koshkin, K. V.; Кошкин, К. В.; Kvasnevskiy, Ye. A.; Квасневский, Е. А.; Grigoryan, T. G.; Григорян, Т. Г. (My University, 2014)
Improving nuclear safety is a vital task of strategic development of the energy sector of Ukraine. Formation of project portfolio is an actual scientific and practical task of nuclear power plants safety improvement. The solution of this problem will shorten the initiation and launch projects and receive additional benefits due to early delivery of energy facilities in operation. The allocation of two phases in decision making is proposed. They are 1) projects analysis and ranking 2) overall portfolio balance assessment. The use of verbal de-cision analysis in project ranking is proposed. The classification of projects based on the use of expert system which implements the soft aspect of decision-making is suggested. The signs of classification for safety improvement projects are shown. Application of verbal analysis and construction of a single ordinal scale allows to automate the process for projects ranking. The use of cognitive modeling for portfolio balance assessment is proposed. The evaluation for portfolio balance based on consideration of the human factor, budgetary constraints and achievement of the needed safety performance is suggested. The implementation of the sug-gested approach allows us to develop the integrated decision support system, aimed at the time reduction for nuclear power plants safety improvement projects implementation. = Предложена модель принятия решений при формировании сбалансиро-ванного портфеля проектов повышения безопасности АЭС, основанная на применении комбинации вербального анализа решений и когнитивного моделирования.
Григорян, Т. Г. Multi-criteria decision making in formation of balanced portfolio of npp safety improvement projects = Многокритериальное принятие решений при формировании сбалансированного портфеля проектов повышения безопасности АЭС / Т. Г. Григорян, Е. А. Квасневский, К. В. Кошкин // Shipbuilding & Marine Infrastructure. – 2014. – № 1 (1). – C. 87–92.
Keywords: project management; nuclear power plants; decision-making; управление проектами; АЭС; принятие решений